Sarcasm in Indonesian Television Show Pesbukers - Fauziah Khairani Lubis; Syamsul Bahri (Randwick International of Social Science Journal, 2023)
Pesbukers' communication style frequently catches the audience's attention since they are not just restricted to the jokes that are hurled but also come with sarcasm, which is presented in each episode. There are many arguments for and against accepting the utilized sarcasm among the audience. The point of the study is to look into the application of sarcasm in the context of the research object, Pesbukers, one of Indonesia's most popular television shows, without any translation process for each dialogue. By employing a qualitative descriptive method, the researcher examined four varieties of sarcasm discovered based on Elisabeth Camp's theory. The results of the study indicate that there are 31 data containing sarcasm. Proportional Sarcasm had the most data (12), followed by Lexical Sarcasm (10), Illocutionary Sarcasm (5), and Like-Prefixed Sarcasm (4). Proportional sarcasm that is straight to the point in utterances pervades all other types of sarcasm. However, the least used sarcasm in this study, like-prefixed sarcasm, is pragmatic and has a meaning contrary to the real motive. The Pesbukers show uses all of the sarcasm subgenres mentioned.